When should advanced planning and scheduling systems be used in sales and operations planning?. Issue 10 (23rd August 2014) - Ivert, Linea Kjellsdotter; Jonsson, Patrik
Abstract : Purpose: We sought to explore how the context affects successful use of APS systems in S&OP processes, and how individual, technological, and organizational (ITO) dimensions affect this procedure. Design/methodology/approach: This is a qualitative case study of two APS system- supported S&OP processes. The work aims to generate propositions concerning the relationships among the use of APS system, the context, ITO dimensions, and fulfillment of S&OP aims. Findings: Use of APS systems was especially appropriate in support of S&OP processes in complex planning environments and when S&OP aims were ambitious. ITO dimensions were important influences on successful APS system use in most contexts. APS systems were not considered appropriate when having S&OP processes with ambitious aims and low individual and organisational maturities. Use of APS systems was also inappropriate when the extent of technological maturity was minimal. S&OP processes with ambitious aims, operating within a complex planning environment, are difficult if not impossible to implement without the support of APS systems. Practical implications: Our suggestions on when APS systems should be used in different S&OP environments will be useful to companies implementing or about to implement APS systems. Originality/value: APS systems offer great potential if they are effectively used to support S&OP, still the use of APS system in S&OP is unexplored. We show how the context and the ITO dimensions affect the successful use of APS systems in S&OP processes.